IMPLEMENTASI METODE AL-HIDAYAH DALAM PEMBELAJARAN BACA TULIS AL-QUR’AN - Agus Kurnia (Jurnal Tatsqif, 2017)
Learning, especially studying Koran, is obligatory for every Muslims. the condition of Muslim children at early age in urban areas especially in Bandung age 6 to 13 years allegedly almost 80% have not been able to read the Koran, therefore Al-Hadi Middle School (SMP) feels obliged to overcome these problems by requiring all students to learn read and write the Koran through Local Subject that is read and write the Koran. To achieve the effectiveness of learning, Al-Hidayah Method is used which is adjusted to the conditions and objectives of learning Read and Write Koran in school. The research used is Analytic Descriptive Method based on observation result, in-depth interview and test conducted. The result of this research shows Al-Hidayah method in Al-Hadi middle school implemented by using classical pattern, individual and cooperative learning. The obstacle is the lack of learning modules and not yet mastered the concept of learning the method of al-hidayah. While the superiority seen in the shortness of existing materials and exercises that enable students to achieve basic competence in reading and write Koran is shown from the number of students who can achieve the basic competencies that have been set.